The need to particularise the concept of spirituality within mental health services in Malaysia - Mohamad Shariff, Nurasikin; Lee, Siew Pien (IIUM Press, 2018)
People with mental health problem in Malaysia require access to spiritual care from their mental health services. However, the literature, which is dominated by Western scholars, brings the broad conception of spirituality into debate, which does not fit the paradigm of the religious worldview in countries such as Malaysia. This paper provides a narrative overview of the tensions inherent in the concept of spirituality as delivered in the literature. It begins a discussion on the place of spirituality in mental health care while highlighting the problematic concept of spirituality currently seen in the literature. This paper thus provides recommendations for future research on the need for particularising the concept of spirituality within mental healthcare in Malaysia.